(untitled) (Annals of Medical Research, 2023)
Aim: Cancers are Turkey’s second most common cause of mortality, following cardiovascular diseases. Tobacco and obesity are the two major etiological factors for cancer progression, which are highly prevalent in Turkey. This study aimed to evaluate the new cancer cases in Turkey attributable to these two main risk factors. Materials and Methods: The tobacco-related cancers based on the International Agency for Research on Cancer (IARC) monographs were esophagus, oral cavity, gastric, pancreatic, larynx, lung, renal, and bladder cancers, and the obesity-related cancers based on the IARC’s and World Cancer Research Fund (WCRF)/American Institute for Cancer Research (AICR) Continuous Update Project’s reports were esophagus, colon, rectum, gallbladder, pancreas, kidney, ovary, endometrium, and breast cancers. The cancer incidences were obtained from the national cancer statistics. A lag time of at least 10 years was considered adequate to observe past exposures’ effects on new cancer cases. The prevalence of tobacco smoking was based on the Peto-Lopez approach. The obesity prevalence was obtained from the National Burden of Disease and Cost-Effectiveness Project Household Survey, 2003 Report in Turkey. Using these incidence and prevalence data, we estimated the population-attributable fractions (PAF) of cancers attributable to smoking and obesity in Turkey. Results: For tobacco-related cancers, the highest PAFs were found in lung cancer (89.8%), larynx cancer (86%), oral cavity and pharynx cancer (77.2%) in males, and larynx cancer (46.5%), lung cancer (43%), and esophagus cancer (31.4%) in females. For obesity-related cancers, the highest PAFs were found in esophagus adenocarcinoma (31.4%), kidney cancer (19.8%), gallbladder cancer (15.1%) in males, and esophagus adenocarcinoma (33.9%), endometrium cancer (32.8%), and postmenopausal breast cancer (22.8%) in females. When all tobacco-related cancers were considered, 41,283 cases in males and 3,853 cases in females were attributable to tobacco smoking, and when all obesity-related cancer types were considered, the number of attributable cancer cases to obesity was 2,653 in men and 7,387 in women Conclusion: The current avoidable cancer burden in Turkey shows that eliminating tobacco smoking and obesity may prevent more than 50,000 cancer cases in Turkey.